Sustainable poverty reduction in less-favoured areas [ - Kuyvenhoven, Arie; Pender, J.; Ruben, Ruerd (CABI, 2007)
The 19 chapters included in this book provide an overview of research conducted within the framework of the collaborative research programme on 'Regional Food Security Policies for Natural Resource Management and Sustainable Economies' (RESPONSE). Theprogramme aimed to identify strategic options for agricultural and rural development in less-favoured areas and policy instruments than enhance rural household's investments in improved and sustainable natural resource management. Through the study of less-favoured areas in Africa, Latin America and Southeast Asia, development pathways allowing for the careful adjustment of resource use strategies at the field, farm-household and village levels are explored. The book consists of five sections under the following headings: (i) development strategies for poor people in less-favoured areas; (ii) resource management options; (iii) livelihoods and food security; (iv) markets and institutional development; and (v) strategies and policy priorities. This text is intended for researchers and students as well as policy makers and economists. The book has a subject index.